Interpreting in Nazi concentration camps - Wolf, Michaela HerausgeberIn; Levi, Primo VerfasserIn von ergänzendem Text (Literatures, cultures, translation, 2016)
"Innovative anthology that brings together leading figures in both translation studies and Holocaust studies to explore the role of interpreting in shaping life in Nazi concentration camps and the encompassing ethical questions that are raised about interpreting in general"--